The Spirit and the Scriptures: Revisiting Cyprian's Use of Prosopological Exegesis - Hughes, Kyle R. (Journal of early Christian history, 2018)
While recent research into the early Christian reading practice of prosopological exegesis, which seeks to identify various persons (prosopa) as the "true" speakers or addressees of a scriptural text in which they are otherwise not in view, has highlighted the complexities involved in attempts to identify the Holy Spirit as the prosopological speaker of Old Testament quotations, there remains a need for clear criteria by which scholars can distinguish between different forms of the Spirit's speech. Building on terminology suggested by Matthew Bates, this article proposes just such a means of distinguishing between when the Spirit functions as the primary speaking agent and when it functions as an inspiring secondary agent, with the former endowing the Spirit with a sufficient degree of theodramatic personhood to make its speech truly prosopological in nature. Applying this criteria to an analysis of Cyprian of Carthage's use of prosopological exegesis in On Works and Alms (De opere et eleemosynis), this article challenges the conclusions of David Downs by demonstrating that the Spirit does not truly speak from its own person in this treatise, though Cyprian may make some moves in this direction elsewhere in his writings. As a result of this study, we have not only a means of better assessing the extent of the pneumatological discontinuity between Cyprian and his Carthaginian predecessor Tertullian but also a clearer path forward for future scholarship that seeks to investigate how early Christian writers conceived of the relationship between the Spirit and the Scriptures.